2021
DOI: 10.31125/hunhemsire.907830
|View full text |Cite
|
Sign up to set email alerts
|

Hemşirelik Öğrencilerinde Eğitim Stresi Algısı ile İnternet Bağımlılığı Arasındaki İlişki

Abstract: Bu araştırmada, hemşirelik öğrencilerinin eğitim ile ilgili algıladıkları stres ve internet bağımlılığı arasındaki ilişkinin incelenmesi amaçlanmıştır. Gereç ve Yöntem: Tanımlayıcı tipteki bu araştırma Mart-Nisan 2016 tarihleri arasında 258 öğrenci ile gerçekleştirilmiştir. Verilerin toplanması için Hemşirelik Eğitimi Stres Ölçeği ve İnternet Bağımlılığı Ölçeği kullanılmıştır. Verilerin istatistiksel değerlendirilmesinde Mann-Whitney U, Kruskal Wallis Test ve Spearman Korelasyon Testi kullanılmıştır. Bulgular:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
2
0
0
1
Order By: Relevance
“…Recent international studies have shown that nursing students experience different levels of stress during their education (Admi, Moshe-Eilon, Sharon & Mann, 2018;Baluwa, Lazaro, Mhango & Msiska, 2021;Suarez-Garcia, Maestro-Gonzalez, Zuazua-Rico, Sanchez-Zaballoz & Mosteiro-Diaz, 2018;Shariff & Azlan, 2021). Moreover, similar studies performed in Turkey support our findings (Büyükbayram & Ayık, 2020;Can, et al, 2019;Demirbağ, Bulut & Çalık, 2021;Ergin, Çevik & Pakiş, 2018;Fırat-Kılıç, 2018;Karabulut, Gurcayir & Yildiz, 2021;Köse, et al, 2021;Senturk & Dogan, 2018;Yılmaz-Karabulutlu et al, 2019). Unlike other departments, theoretical education and practical education are given concurrently in nursing education.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Recent international studies have shown that nursing students experience different levels of stress during their education (Admi, Moshe-Eilon, Sharon & Mann, 2018;Baluwa, Lazaro, Mhango & Msiska, 2021;Suarez-Garcia, Maestro-Gonzalez, Zuazua-Rico, Sanchez-Zaballoz & Mosteiro-Diaz, 2018;Shariff & Azlan, 2021). Moreover, similar studies performed in Turkey support our findings (Büyükbayram & Ayık, 2020;Can, et al, 2019;Demirbağ, Bulut & Çalık, 2021;Ergin, Çevik & Pakiş, 2018;Fırat-Kılıç, 2018;Karabulut, Gurcayir & Yildiz, 2021;Köse, et al, 2021;Senturk & Dogan, 2018;Yılmaz-Karabulutlu et al, 2019). Unlike other departments, theoretical education and practical education are given concurrently in nursing education.…”
Section: Discussionsupporting
confidence: 85%
“…Most students who participated in the research were female and 20 years old or younger. Other studies on the present topic were seen to have similar sample groups (Can, Çuvalci & Hindistan, 2019;Köse, Ayhan, Taştan, İyigün & Özçakır, 2021). This is an expected result when it is considered that females more choose the nursing department and that students may have won a place in the nursing department in the year in which they entered the university exam.…”
Section: Discussionsupporting
confidence: 75%
“…Bu stresi tetikleyen ya da etkileyen pek çok faktör sıralanmaktadır. Özellikle hastanın ağrı deneyimi ya da hayatını kaybetmesi, acil müdahale gereklilikleri, meslek derslerine yönelik teorik bilgi ya da pratik uygulamalarda beceri yetersizliği, hastaya zarar verme korkusu gibi konular öğrencilerde stresin artmasına neden olabilmekte ve öğrenciler yaşanan bu stres faktörleri ile baş etmeye çalışmaktadır (2,3). Öğrencinin hemşirelik eğitimi sürecini başarılı bir şekilde tamamlayarak, mesleğe yönelik istenilen seviyede bilgi ve beceri kazanımı için yaşanılan stresin yönetimi önemlidir.…”
Section: Introductionunclassified